Anabolic effects of vitamin D and magnesium in aging bone. Issue 193 (October 2019) - Erem, Sarah; Atfi, Azeddine; Razzaque, Mohammed S.
Highlights: Magnesium is important for vitamin D activation. Under-consumption of magnesium is widespread in the USA and beyond. Magnesium deficiency is associated with numerous chronic diseases. Optimal intake of vitamin D and magnesium are essential for healthy life. Abstract: Decreased bone mass and an increased risk of bone fractures become more common with age. This condition is often associated with osteoporosis and is caused by an imbalance of bone resorption and new bone formation. Lifestyle factors that affect the risk of osteoporosis include alcohol, diet, hormones, physical activity, and smoking. Calcium and vitamin D are particularly important for the age-related loss of bone density and skeletal muscle mass, but other minerals, such as magnesium, also have an important role. Here, we summarize how optimal magnesium and vitamin D balance improve health outcomes in the elderly, the role of magnesium and vitamin D on bone formation, and the implications of widespread deficiency of these factors in the United States and worldwide, particularly in the elderly population.